Doses e épocas de aplicação de potássio na cultura da soja em sucessão a plantas de cobertura - Silva, Amilton Ferreira da; Lazarini, Edson [UNESP] (Univ Estadual Londrina, 2014)
Potassium (K) is the second nutrient that is required in larger amounts by soybean crop. With the use of high doses of that nutrient and increase of no-tillage areas in last years, some changes occurred in ways of this nutrient application, as well as the introduction of cover crops in the system for straw formation. Due those facts, the aim with this work was to study doses and times of potassium application for soybean sowed as succession for cover crops in no-tillage system, in a clayey Distrofic Red Latosol, in cerrado region. The experimental design was a randomized block with treatments arranged in 3x3x5 factorial scheme, with the following factors, cover crops: Pearl millet (Pennisetum glaucum) and Proso millet (Panicum miliaceum) and a control (fallow area), rates of K2O (0, 50 e 100 kg ha(-1)) and K2O application forms (100% in the cover crops; 100% at sowing of soybean; 100% in topdressing in soybean; 50% at sowing cover crops + 50% at soybean sowing; 50% at soybean sowing + 50% in topdressing in the soybean) with four replicates. The Pennisetum glaucum as soybean predecessor crop yields higher dry matter content than the Panicum miliaceum in a short period of time. In clay soil with high content of potassium there was no response to the applied potassium levels. Full doses of potassium maintenance fertilization can be applied in the predecessor cover crop, at sowing or topdressing in soybean crop.
Doses and application seasons of potassium on soybean crop in succession the cover crops
Keywords: No-tillage; recycling of nutrients; anticipation of fertilization